Misogynous Economies : The Business of Literature in Eighteenth-Century Britain - Mandell, Laura (Book collections on Project MUSE., 2015)
The eighteenth century saw the birth of the concept of literature as business: literature critiqued and promoted capitalism, and books themselves became highly marketable canonical objects. During this period, misogynous representations of women often served to advance capitalist desires and to redirect feelings of antagonism toward the emerging capitalist order. Misogynous Economies proposes that oppression of women may not have been the primary goal of these misogynistic depictions. Using psychoanalytic concepts developed by Julia Kristeva, Mandell argues that passionate feelings about the a.